Petroleum geology of Ireland - Naylor, D. 1935- (Dunedin Academic Press, 2011)
This book provides a comprehensive review of the petroleum geology of Ireland and its very extensive continental shelf. The authors chart the fifty-year history of petroleum exploration in Ireland, from early drilling onshore to the present frontier exploration in the deep water Atlantic basins. The structural framework and regional geological setting of the sedimentary basins is described in two chapters, and this is followed by a review of the history of Irish onshore and offshore exploration, together with an outline of the licensing framework. The onshore basins, largely Carboniferous and older, are then considered as they guided the initial understanding of the younger offshore geological framework. Pre-Permian to Cenozoic stratigraphy of the region is explained in five chapters, each illustrated by palaeogeographic maps that are based both on onshore geology and on the results of offshore drilling. The major regional groups of basins are then considered and, for each, there is analysis of basin development and petroleum systems, together with a review of their exploration history, plays, and prospects. The Celtic Sea basins, south of Ireland, contain a thick Mesozoic succession and host a number of producing petroleum fields and sub-commercial discoveries. --